1996
DOI: 10.1002/(sici)1097-0169(1996)35:2<94::aid-cm2>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent regulation of cellular ATP concentration, and depolymerization of the interphase microtubular network induced by elevated cellular ATP concentration in whole fibroblasts

Abstract: In the present work, evidence is presented indicating that an increased cellular ATP concentration during mitosis may, in conjunction with other factors [Verde et al., 1990: Nature 343:233–238; Andersen et al., 1994: J Cell Biol. 127:1289–1299], induce depolymerization of the interphase microtubular network in cultured fibroblasts. It is shown here that the cellular ATP concentration varies through the cell cycle, reaching a peak at G2M‐ and minimum at late G1/early S‐phase. Furthermore, we have found, using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
(4 reference statements)
2
20
0
1
Order By: Relevance
“…Early studies suggested that microtubules may act as a sensor of the energy state of the cell (129) with ATP depletion causing instability of detyrosinated microtubule plus ends (130, 131). AMPK is a major sensor for the metabolic state of the cell and affects microtubule dynamics by phosphorylation of CLIP170 (132).…”
Section: Microtubule Cytoskeleton In Stress Responsesmentioning
confidence: 99%
“…Early studies suggested that microtubules may act as a sensor of the energy state of the cell (129) with ATP depletion causing instability of detyrosinated microtubule plus ends (130, 131). AMPK is a major sensor for the metabolic state of the cell and affects microtubule dynamics by phosphorylation of CLIP170 (132).…”
Section: Microtubule Cytoskeleton In Stress Responsesmentioning
confidence: 99%
“…These differences indicate a higher energy charge (24) in SG2M phase cells, suggesting that energy metabolism oscillates over the cell cycle. Oscillation in ATP level was previously reported in synchronized mouse 3T3 fibroblasts (25), and less pronounced oscillation in GTP level in HL-60 cells (26) and in yeast (27), suggesting that the phenomenon is deeply conserved. The nucleoside diphosphokinase enzyme (NDP kinase, encoded by NME1-9 in humans), which synthesizes NTPs from NDPs, was also found to continuously increase in activity during the cell cycle of fission yeast, with highest peak in S phase (28), possibly explaining the simultaneous increase in phosphorylation state of all nucleotides.…”
Section: Oscillating and Housekeeping Central Metabolism In Cycling Cmentioning
confidence: 62%
“…2 to generate two daughter cells. Marcussen and Larsen (1996) indicated that the cellular ATP concentration varies through the cell cycle, reaching a peak at G2/M phase and minimum at late G1/early S-phase. Recently, Chan et al (2013) reported that low concentrations of drugs that arrest the cell cycle at S phase or G2/M phase, induced repairable DNA damage, increase in cell size and amount of ATP per cell.…”
Section: Discussionmentioning
confidence: 99%